Usage of Cell-Free Protein Synthesis in Post-Translational Modification of μ-Conopeptide PIIIA - Yanli Liu; Zitong Zhao; Yunyang Song; Yifeng Yin; Fanghui Wu; Hui Jiang (Marine Drugs, 2023)
The post-translational modifications of conopeptides are the most complicated modifications to date and are well-known and closely related to the activity of conopeptides. The hydroxylation of proline in conopeptides affects folding, structure, and biological activity, and prolyl 4 hydroxylase has been characterized in Conus literatus. However, the hydroxylation machinery of proline in conopeptides is still unclear. In order to address the hydroxylation mechanism of proline in μ-PIIIA, three recombinant plasmids encoding different hybrid precursors of μ-PIIIA were constructed and crossly combined with protein disulfide isomerase, prolyl 4 hydroxylase, and glutaminyl cyclase in a continuous exchange cell-free protein system. The findings showed that prolyl 4 hydroxylase might recognize the propeptide of μ-PIIIA to achieve the hydroxylation of proline, while the cyclization of glutamate was also formed. Additionally, in Escherichia coli, the co-expression plasmid encoding prolyl 4 hydroxylase and the precursor of μ-PIIIA containing pro and mature regions were used to validate the continuous exchange cell-free protein system. Surprisingly, in addition to the two hydroxyproline residues and one pyroglutamyl residue, three disulfide bridges were formed using Trx as a fusion tag, and the yield of the fusion peptide was approximately 20 mg/L. The results of electrophysiology analysis indicated that the recombinant μ-PIIIA without C-terminal amidate inhibited the current of hNaV1.4 with a 939 nM IC50. Our work solved the issue that it was challenging to quickly generate post-translationally modified conopeptides in vitro. This is the first study to demonstrate that prolyl 4 hydroxylase catalyzes the proline hydroxylation through recognition in the propeptide of μ-PIIIA, and it will provide a new way for synthesizing multi-modified conopeptides with pharmacological activity.